(untitled) (Comprehensive Journal of Science, 2026)
It considers chronic kidney failure one of the risk factors that requires continuous follow-up, and considers chronic kidney disease one of the most common causes Viral disease, specific to hepatitis B virus (HBV). The aim of this study is to determine the mode of transmission of HBV virus in chronic kidney failure patients, and to study some of the factors associated with it. This study was conducted on a patient with kidney failure disease, tests were performed using the ELISA test and detected that Age 30 – 39 is the most common cause of hepatitis B. Age 60 – 69 and 70 – 79 is the most common cause of hepatitis B. The number of infected persons increased from 32 (32% ) and non-infected persons from 68 (68%). The results of the existence of a proportion of HBV-infected patients underscore the importance of adherence to preventive and anti-inflammatory measures within the laundry units. The study recommends the necessary of periodic screening for chloroplast disease, and encourages the health prevention program to prevent the spread of these viruses.